Bulgaria : Railways Policy Note - World Bank (Washington, DC, 2013)
Under a succession of reform-minded governments, the Bulgarian rail sector has achieved some ambitious targets-stable traffic volumes and hard-won financial stability that was endorsed by investor confidence during a recent bond issuance for EUR 120 million. Today, all Acquis Communautaires relevant to the rail sector have been adopted. Vertical unbundling of services separated public railway infrastructure from operation of railway transport services; the track access charges that were introduced opened market access to rail infrastructure and allowed cost recovery; and public service contracts were laid out to clarify government contributions to the sector. In addition, Bulgaria's substantial accomplishments in improving railway operating efficiency included reducing the State-owned railway company staff by 40 percent; creating a holding company structure with three legally independent subsidiaries and business lines-freight, passengers, and traction services. The various roles of the State in Bulgaria's rail industry- policymaker, regulator, owner, and client require a cultural change if Government is to optimize the balance among public policy choices, entity management constraints, and available fiscal space. Overcoming the railway industry's challenges will be difficult and should not be underestimated; the current financial crisis will appear to militate against immediate action in an investment-intensive sector such as infrastructure, but the railway industry in Bulgaria has never been better positioned to move forward. Postponing the completion phase of railway reform will not only squander future economic prospects through continued asset deterioration and loss of market share, but also lay waste to the past investments that have brought the country so far along in attaining today's railway market position and financial stability.